Immunomodulatory acidic polysaccharides from Zizyphus jujuba cv. Huizao: Insights into their chemical characteristics and modes of action. (30th August 2018) - Zou, Man; Chen, Yilun; Sun-Waterhouse, Dongxiao; Zhang, Yuhuan; Li, Feng
Highlights: Two acidic polysaccharides were obtained from Zizyphus jujuba cv. Huizao. HP1 and HP2 had the same monosaccharide species and manganese content. HP1 and HP2 differed in molar ratio of monosaccharides, Mw and uronic acid content. Both HP1 and HP2 enhanced nonspecific and specific responses in the mice. The activities of two polysaccharides were related to their chemical characteristics. Abstract: Chinese jujube is commonly used in folklore medicine. This study aimed to examine the in vivo immunomodulatory activity of two acidic polysaccharides, HP1 and HP2, extracted and purified from Zizyphus jujuba cv. Huizao (which remains extensively unexplored). HP1 and HP2 had the same monosaccharide species and manganese contents, but differed in their molar rhamnose, arabinose, mannose, glucose, galactose and uronic acid contents (7.32 and 35.9%, as galacturonic acid), Mw (68.7 and 111 kDa, respectively), and contents of K, Cr, Cu, Zn, Pb and Ca. Both HP1 and HP2 could significantly ( P  < 0.05) increase spleen and thymus indices, promote serum hemolysin formation, enhance the phagocytic activity of macrophages and inhibit footpad edema of mice, with HP2 likely being a more consistent and potent immunomodulator. This study clearly demonstrates the potential of Z. jujuba cv. Huizao polysaccharides as immunomodulators and their associated chemical characteristics and working mechanisms.